2001
DOI: 10.1073/pnas.141048498
|View full text |Cite
|
Sign up to set email alerts
|

A novel mammalian receptor for the evolutionarily conserved type II GnRH

Abstract: Mammalian gonadotropin-releasing hormone (GnRH I: pGlu-His-TrpSer-Tyr-Gly-Leu-Arg-Pro-Gly-NH 2) stimulates pituitary gonadotropin secretion, which in turn stimulates the gonads. Whereas a hypothalamic form of GnRH of variable structure (designated type I) had been shown to regulate reproduction through a cognate type I receptor, it has recently become evident that most vertebrates have one or two other forms of GnRH. One of these, designated type II GnRH (GnRH II: pGlu-His-Ser-His-Gly-Trp-Tyr-Pro-Gly-NH 2), is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
271
0
10

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(286 citation statements)
references
References 48 publications
5
271
0
10
Order By: Relevance
“…The bullfrog type I GnRH receptor was shown to internalize via a β-arrestin and dynamin-dependent pathway, whereas the bullfrog type II and III GnRH receptors internalize via a pathway that is β-arrestin-independent, but dynamin-dependent, similar to the pathway utilized by the chicken GnRH receptor [1,114]. Unlike all the mammalian type I GnRH receptors, the cloned marmoset type II GnRH receptor [94] has a carboxyl-terminal tail, and a study identified a serine-doublet in the carboxyl-terminal tail as critical for internalization of the type II GnRH receptor and suggested that these residues undergo phosphorylation by GRKs. However, neither of these residues, nor the carboxyl-terminal tail, was shown to be required for β-arrestin-dependent internalization [123].…”
Section: Absence Of Rapid Desensitization and Ligand-induced Internalmentioning
confidence: 99%
See 1 more Smart Citation
“…The bullfrog type I GnRH receptor was shown to internalize via a β-arrestin and dynamin-dependent pathway, whereas the bullfrog type II and III GnRH receptors internalize via a pathway that is β-arrestin-independent, but dynamin-dependent, similar to the pathway utilized by the chicken GnRH receptor [1,114]. Unlike all the mammalian type I GnRH receptors, the cloned marmoset type II GnRH receptor [94] has a carboxyl-terminal tail, and a study identified a serine-doublet in the carboxyl-terminal tail as critical for internalization of the type II GnRH receptor and suggested that these residues undergo phosphorylation by GRKs. However, neither of these residues, nor the carboxyl-terminal tail, was shown to be required for β-arrestin-dependent internalization [123].…”
Section: Absence Of Rapid Desensitization and Ligand-induced Internalmentioning
confidence: 99%
“…Furthermore, analysis of DNA sequence data and functional studies indicate that there has been sporadic silencing or deletion of GnRH II and/ or the type II receptor in various mammals. Thus, GnRH I and GnRH II and the type I and type II GnRH receptors are expressed in some primates such as the marmoset [94] and green monkey while the type II GnRH receptor has been silenced in man and the chimpanzee by stop codons and frame shifts [101]. From a molecular genetics point of view, it is possible that, during evolution, the mammalian type II GnRH receptor gene came under functional pressure by close apposition of 5′ and 3′ anking genes (potentially leading to interference with transcription) and subsequent mutations led to gene silencing.…”
Section: Silencing Of Gnrhs and Gnrh Receptors In Mammalsmentioning
confidence: 99%
“…As I said above the cDNA for the receptor of GnRH II has been cloned in amphibians, its homologs in primates have been sequenced (Millar et al 2001, Neill et al 2001, and their locations ascertained, thus leading to an investigation of functions of GnRH II other than hypophysiotropic ones.…”
Section: Lrf Lhrh Gnrhmentioning
confidence: 99%
“…Although GnRH-based vaccines have been produced for use as contraceptives in animals [35], their development so far for use in humans has been aimed primarily at treating sex hormone-dependent diseases including cancer [24,36]. It has also become apparent that GnRH exists in several different forms and that these isoforms can bind with differing selectivities to different GnRH receptors [37,38]. These findings clearly have implications for the specificity and safety of GnRH-based vaccines.…”
Section: Gonadotropin-releasing Hormone (Gnrh)mentioning
confidence: 99%